2012
DOI: 10.1111/jcap.12006
|View full text |Cite
|
Sign up to set email alerts
|

Underaged Patients' Opinions Toward Different Containment Measures: A Questionnaire Survey in Finnish Adolescent Psychiatry

Abstract: Adolescents disapprove of containment measures some of which are widely used in psychiatric practice. Their opinions differ significantly from those of the staff. New ways to manage crisis situations should be developed. Where containment cannot be avoided, information, explanation about the procedures involved, and debriefing should be offered to an underaged patient in a manner which takes account of his/her developmental level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In line with several publications ( 29 , 30 , 54 ), Swiss patients, NOK, and HCP most clearly rejected the net bed. This measure is not applied in Switzerland and is likely, as in Finland, perceived as “inhumane and cruel” ( 28 ). Mechanical restraints and seclusion were rejected second- and third-most by all groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with several publications ( 29 , 30 , 54 ), Swiss patients, NOK, and HCP most clearly rejected the net bed. This measure is not applied in Switzerland and is likely, as in Finland, perceived as “inhumane and cruel” ( 28 ). Mechanical restraints and seclusion were rejected second- and third-most by all groups.…”
Section: Discussionmentioning
confidence: 99%
“…The Attitudes to Containment Measures Questionnaire (ACMQ) is a self-rating paper-and-pencil questionnaire that has been validated ( 38 ) and used in several publications from different countries, and thus from different cultures ( 24 , 25 , 28 , 30 , 39 , 48 55 ). One disadvantage of the ACMQ is that it also collects data on coercive measures that are uncommon or not used at all in Switzerland, such as the net bed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found varying attitudes towards containment measures in patients and HCP [15, 16]. Furthermore, it was shown that not only patients‘ characteristics or preferences but also the traditions and policies of the respective clinics influence the decision for or against specific containment measures [17].…”
Section: Introductionmentioning
confidence: 99%
“…In two of the studies, children were asked about their opinion on different practices to manage crises (Hottinen et al . ; Kazdin ). In these studies, the different interventions children had to rate or comment on were all coercive; no information was provided on what alternatives children might suggest.…”
Section: Introductionmentioning
confidence: 99%